Diagnostic Test On Modified Score Of Cesarean Section History In Placenta Accreta Index In Predicting Placenta Accreta Diagnosis In Rsup Dr M Djamil - Widayat, Widayat; Friadi, Andi; Bacthiar, Hafni (Fakultas Kedokteran Universitas Andalas, 2021)
Introduction : Placenta accreta is defined as abnormal implantation of placenta villi which invades myometrium without the presence of decidua bacalis resulting in placenta that is difficult to remove. Based on the depth of invasion, placenta accreta is divided into three grades, placenta accreta, placenta increta, and placenta percreta. Placenta accreta developes if chorionic villi attaches to endometrium beyond desidua basalis. Placenta increta develops when chorionic villi invades the whole myometrium. Placenta percreta developes when chorionic villi attaches beyond myometrium reaching serous and abdominal organ. Based on clinical manifestation, placenta accreta is the common term being used. Incident of abnormal placenta invasion varies from 1 : 93.000 up to 1 : 540 pregnancy. PA incidence had increased four times from 1994 to 2002 in line with increased of caesarean section procedure. Other study showed history of caesarean section increased risk of placenta accreta up to 8,7 times. Placenta accreta index (PAI) was developed based on scoring process or various parameters assessment to help diagnose placenta accreta. The parameters including: history of caesarean section ≥ 2 times, lacunae grade, sagittal smallest myometrial thickness, anterior placenta previa and birding vessel. High PAI indicates high risk of abnormal placenta invasion based on histology.Objective : This study aims to investigate modified history of cesarean section score in placenta accreta index in predicting placenta accreta diagnosis in RSUP DR M Djamil Padang.Material and methods : This was analytical study with cross sectional design. Study population was 84 placenta accreta patients in RSUP Dr. M. Djamil Padang from 2016 to 2019. Study sample was recruited using simple random sampling technique after meeting inclusion and exclusion criteria. Statistic analysis was done using Cohen’s Kappa test. Diagnostic test including sensiticivy, specivicity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy.Result : Strenght of agreement diagnosis placenta accreta based on PAI showed Kappa score of -0,002 (Kappa score < 0,2) which indicated poor strength of agreement. Strenght of agreement diagnosis placenta accreta based on modified PAI showed Kappa score of 0,353 (Kappa score range from 0,21 to 0,40) which indicated fair strength of agreement. PAI diagnostic test yield sensitivity of 97,1%, specificity of 2,8%, positive predictive value of 48,5%, negative predictive value of 50%, and accuracy of 48,6%. Modified PAI diagnostic test yield sensitivity of 97,1%, specificity of 38,9%, positive predictive value of 60%, negative predictive value of 93,3%, and accuracy of 67,1%.Conclusion : PAI has high sensitivity, low specificity, moderate positive predictive value, moderate negative predictive value, and moderate accuration. Modified PAI has high sensitivity, moderate specificity, moderate positive predictive value, high negative predictive value, and high accuracy. PAI diagnosis has poor strength of agreement compared with pathology anatomy. Modified PAI diagnosis has fair strength of agreement compared with pathology anatomy. Modified PAI has identical sensitivity with standard PAI, meanwhile for specificity, positive predictive value, negative predictive value, and accuracy, modified PAI yields higher result compared to PAI.Keywords: Modified score of history caesarean section, placenta accreta index, Modified placenta accreta index, diagnostic test of placenta accreta diagnosis